Preparation of standardized rhinacanthus nasutus leaf extract by green extraction methods and evaluation of antifungal activity of its topical solution against trichophyton rubrum - Shakya, Karun (Prince of Songkla University, 2016)
Thesis (M.Pharm., Clinical Pharmacy)--Prince of Songkla University, 2015